Black carbon footprint of human presence in Antarctica - Cordero, Raul R.; Sepulveda, Edgardo; Feron, Sarah; Damiani, Alessandro; Fernandoy, Francisco; Neshyba, Steven; Rowe, Penny M.; Asencio, Valentina; Carrasco Cerda, Jorge Fernando; Alfonso, Juan A.; Llanillo, Pedro; Wachter, Paul; et al. (My University, 2022)
The snow surrounding research facilities and shore tourist-landing sites in Antarctica was found to be darker than elsewhere in the continent, which suggests that local emissions of black carbon are accelerating seasonal snowmelt in impacted regions. Black carbon (BC) from fossil fuel and biomass combustion darkens the snow and makes it melt sooner. The BC footprint of research activities and tourism in Antarctica has likely increased as human presence in the continent has surged in recent decades. Here, we report on measurements of the BC concentration in snow samples from 28 sites across a transect of about 2,000 km from the northern tip of Antarctica (62 degrees S) to the southern Ellsworth Mountains (79 degrees S). Our surveys show that BC content in snow surrounding research facilities and popular shore tourist-landing sites is considerably above background levels measured elsewhere in the continent. The resulting radiative forcing is accelerating snow melting and shrinking the snowpack on BC-impacted areas on the Antarctic Peninsula and associated archipelagos by up to 23 mm water equivalent (w.e.) every summer.
Keywords: Snowpack; Carbon Footprint; Archipelago; Peninsula